PENGARUH GREEN PURCHASING BEHAVIOR TERHADAP BRAND LOYALTY PADA KONSUMEN LBP - Srimulyana, Aribah; Eryandra, Alvin (Jurnal Ilmiah Penelitian Psikologi, 2021)
Environmentally friendly purchasing behavior arises because of the urgency of environmental issues in various parts of the world, including Indonesia. This has also encouraged many companies to produce environmentally friendly products, thereby increasing competition between companies. Competition is unavoidable in the business world and becomes a challenge to win loyalty from consumers. This study aims to examine whether there is an effect of environmentally friendly buying behavior on brand loyalty in love, beauty and planet consumers. Respondents who participated in this study were 164 people. The measuring instrument used consists of 4 statements adapted from Kaman Lee (2008) for green purchasing behavior and 4 statements from Chaudhuri & Holbrook (2001) for brand loyalty. . The results of the regression analysis in this study indicate that environmentally friendly purchasing behavior contributes to the formation of brand loyalty by 28.2% (<0.001). This means that environmentally friendly purchasing behavior has a significant positive effect on the formation of brand loyalty